BIOMECHANICAL EVALUATIONS OF IMPLANTO-PROSTHETIC RESTORATIONS - Resmerita Andreea; Cretu Cosmin Ionut; Scheuleac Alexandra; Agop-Forna Doriana; Adam Eduard; Forna Norina (Romanian Journal of Medical and Dental Education)
Aim of the study: This study aims to evaluate the biomechanical effects of various prosthetic configurations in cases of severe bone atrophy. Short dental implants (≤8 mm) and narrow diameter implants (NDI) ≤3.5 mm were proposed as alternatives to bone augmentation procedures, showing encouraging short-term survival rates. The implants were later restored with zirconia prostheses, using splinted or single crown designs. Dental implants of 4 mm, 6 mm, and 8 mm length, and diameters of 3.3 mm and 3 mm in atrophic posterior mandibular bone were discussed.